ANALISIS HUBUNGAN ANTARA LEVERAGE, EPS DAN DPS PADA SEKTOR RETAIL TRADE YANG TERDAFTAR DI BURSA EFEK INDONESIA SELAMA PERIODE 2003–2006 - Astriana Madjid; Ida . (Jurnal Bisnis dan Ekonomi, 2010)
The aim of this research is to test relation between Operating Leverage and Earning BeforeInterest and Tax (EBIT), EBIT and Earning Per Share (EPS), financial leverage with EPS andDividen Per Shares(DPS) , and relation between EPS and DPS. The samples of this research are8 companies at commerce industry of retail trade in Indonesia Stock Exchange (ISX) by selectedbased on purposive sampling. The result shows that positive relationship between EBIT and EPS,and there are no positive relationship between DOL and EBIT, DFL and EPS, DFL and DPS, EPSand DPS.Keywords: operating leverage, financial leverage, earning before interest tax (EBITt), earningper share(EPS) and dividend per share (DPS).